Being recognized in an algorithmic system: Cruel optimism in gay visibility on Douyin and Zhihu - Wang, Shuaishuai; Zhou, Oscar Tianyang (Sexualities, 2024)
Drawing upon “algorithmic ethnography” (Christin, 2020), this article enrolls algorithms to gather qualitative data to examine how Chinese social media platforms and their algorithms intersect with gay visibility. By looking critically into the ways that gay romance and HIV-related content are generated on Douyin and Zhihu, respectively, we argue that algorithmic gay visibility serves as a form of cruel optimism, which becomes a profitable convenience for corporate social media platforms and operates in an exclusionary matrix. The content that ordinary Chinese gay men are presented with (for example, the able-bodied, romanticized normative gay relationship and overly optimistic self-help advice for gay men living with HIV) is economically viable, which produces trending and monetizable items, including music tracks, viral dance routines and challenges, personas, medicine promotions, as well as commercial healthcare training and marketing. In contrast, non-conforming bodies, non-monogamous and queer relationships, as well as the depression, stigma and discrimination experienced by gay men living with HIV are algorithmically invisible.